INVENTORY OF ANACARDIACEAE FAMILY AT SUNAN GUNUNG DJATI STATE ISLAMIC UNIVERSITY - Nazla Fauziyah Octaviani; Nisa Hamidah Zahra Ar-Rais; Ateng Supriyatna (Student Scientific Creativity Journal, 2023)
Indonesia is a country with a tropical climate, so it can produce high diversity, and plants adapt. This includes educational areas with green areas and a fairly even level of diversity, especially in the Anacardiaceae family with special characteristics, such as woody trees, resin channels, plants belonging to the shrub habitus, and single and compound leaves. This study used cruise methods or cruising methods by calculating and analyzing the actual situation in the environment of State Islamic University Sunan Gunung Djati Campus I. There were two genera and three species found, namely the genus Spondias with its species Spondias pinnata or amra and the genus Mangifera with its species Mangifera indica or mango and Mangifera odorata or kweni.